1950
DOI: 10.3181/00379727-73-17604
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mucopolysaccharides in Pathogenesis of Experimental Exophthalmos.

Abstract: In the course of investigations of hormonal effects on connective tissue in these laboratories, our attention was drawn to the problem of localized myxedema. As a result of our clinical impression that ,this lesion was often associated with progressive exophthalmos, the studies to be reported here were initiated. Recently, Curtis(1) has also pointed out that the two conditions occur frequently in the same patient, and have a very similar clinical course.The primary pathological change in localized myxedema is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1956
1956
1989
1989

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Pituitary extracts produce exophthalmos and an accumulation of glycosaminoglycans in retro-orbital tissue when injected into several classes of animals (1)(2)(3)(4)(5). In previous work, we demonstrated that the exophthalmogenic activity of these extracts could be ascribed to thyrotropin (TSH) (6) but that partial digestion of purified TSH with pepsin could result in an exophthalmogenic fragment of the TSH molecule that had no thyroid-stimulating activity (7).…”
mentioning
confidence: 99%
“…Pituitary extracts produce exophthalmos and an accumulation of glycosaminoglycans in retro-orbital tissue when injected into several classes of animals (1)(2)(3)(4)(5). In previous work, we demonstrated that the exophthalmogenic activity of these extracts could be ascribed to thyrotropin (TSH) (6) but that partial digestion of purified TSH with pepsin could result in an exophthalmogenic fragment of the TSH molecule that had no thyroid-stimulating activity (7).…”
mentioning
confidence: 99%
“…The infiltrate disappears from the skin of patients with generalized myxedema who are given 120 to 180 mg. of desiccated thyroid daily for six to eight weeks (1). A deposit, histochemically like that which occurs in generalized myxedema, occasionally presents locally in the pretibial skin of patients with thyrotoxicosis and exophthalmos (2,3). When the patient with localized pretibial myxedema is given 180 mg. of desiccated thyroid a day, however, no clinical or histochemical change occurs in the myxedematous plaque.…”
mentioning
confidence: 99%
“…Mucopolysaccharides, particularly hyaluronic acid, were present in the orbital tissue of these patients (Ludwig, Boas & Soffer, 1950;Asboe-Hansen & Iverson, 1951) and have been produced in both intact and thyroidectomized animals by the injection of thyrotropin. It is therefore proposed that the histological features described in thyrotoxic myopathy, apart from muscle atrophy, are probably due to the effect of a pituitary factor.…”
Section: Prognosismentioning
confidence: 95%